Global health nephrology education collaboration: a US–Kenya experience - Owino, Christopher; Mutugi, Ann; Shah, Binoy; Gaffney, Mary; Koech, Mathew; Tang, Jie (Frontiers in Medicine, 2025)
IntroductionChronic kidney disease (CKD) is a growing contributor to morbidity and mortality in Sub-Saharan Africa. In response to regional workforce and training gaps, Moi University (MU) in Kenya and Brown University (BU) in the United States launched a collaborative nephrology education initiative in 2018 to strengthen clinical capacity in Western Kenya.MethodsIn 2019, stakeholder consultations identified key gaps in nephrology education. Targeted interventions were implemented, and a follow-up survey was conducted in 2023 among MU and BU participants to evaluate the program’s impact.ResultsAt baseline in 2019, only 9% of 45 surveyed clinicians reported confidence in managing nephrology patients, and 26% had participated in a nephrology education session in the previous 3 years. In response, biweekly virtual case-based conferences were initiated for MU internal medicine residents, who were later invited to join BU’s nephrology conferences and journal clubs. A jointly led annual West Kenya Nephrology Conference began in 2018, and since 2019, a senior BU nephrology faculty member has provided annual on-site bedside teaching. By 2023, 96.6% of respondents reported improved confidence in nephrology care. BU nephrology fellows participating in the collaboration reported enhanced understanding of kidney disease management in global contexts. Planned next steps include community outreach, collaborative clinical and epidemiological research, and the development of the first nephrology fellowship program in Western Kenya.ConclusionThis collaboration demonstrates a sustainable model for international nephrology education partnerships, with measurable benefits for both institutions. The approach may serve as a blueprint for other programs seeking to build global capacity in nephrology care and training.